Tinjauan Yuridis Cyber Bullying Dalam Ranah Hukum Indonesia - Ni Putu Suci Meinarni (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
To find out if there are some regulations governing cyber bullying in Indonesia, it is necessary to examine further the relevant laws. This article using a judicial normative approach in providing interpretations of laws related to cyber bully actions in cyberspace. Those are, the Criminal Law, Child Protection Act (related to bullying of children), as well as the Law of Information and Electronic Transactions(related to locus). Each of the Act has a linkage to each other, Which can be used as a reference in determining the potential crime arise from bullying. Thus, hopefully the society as a legal subject will have deep understanding about ethics and regulations applied in cyberspace concerning to bullying.